Lack of Parental Attention to Early Childhood Behavior in the Village of Timbang Lawan - Ade Chita Putri Harahap; Apriana Dewi; Siti Komariah Sipahutar; Jihanda Nafisha; Maruba Alianna Daulay (Edumaspul: Jurnal Pendidikan, 2022)
Parental parenting is very important for child development, especially early childhood. Early childhood is a very sensitive time, because parents must be able to provide positive things to help children’s psychological and mental growth as well as the community in Timbang Lawan Bahorok Village. In the implementation of the study we used the interview method as an instrumental tool. During a visit to the village of Timbang Lawan Bahorok we found that many parents ignored the impotance of parenting and support involving children. We also see a lack of parental readness in educating. They think that the role of parents is an easy thing, which is only limited to feeding, sending and caring, but basically parents are the main key to the child’s psychic and emotional development. As parent’s, they should pay more attention, understand and get closer to the child. If the parenting style given by the parents is good, the child will bring out a good attitude and have good character.